The Role of Diplomacy through Agreements General Agreement on Tariffs and Trade (GATT) Geopolitics in the Pacific War - Aliyah, Yurizki; Prakoso, Lukman Yudho; Alam, Tasdik Mustika; Patmi, Sri (Formosa Journal of Applied Sciences, 2024)
Diplomacy through international agreements such as the General Agreement on Tariffs and Trade (GATT) has an important role in international relations and geopolitics. This study aims to analyze the role of diplomacy through GATT in the context of the Pacific War as well as its impact on geopolitical dynamics in the region. Research methods used include literature study and analysis of historical documents to trace GATT's role in defusing trade conflicts between countries involved in the Pacific War. The results of the analysis show that diplomacy through GATT can reduce trade barriers between countries in conflict, thus helping to minimize the impact of the Pacific War on the global economy. The discussion included an explanation of how the role of diplomacy through GATT helped build more stable trade relations in the post-World War II Pacific region.